Canadian Gamexpo '94 : conference proceedings ... : Gamexpo '94 ... - Native Investment And Trade Association; Hoegg, John E. (Native Investment & Trade Association, 1994)
Sessions in table of contents: The big picture : mainstream gaming in Canada and Successful First Nations gaming in Canada III. ...